Effect of zearalenone on reproductive parameters and expression of selected testicular genes in mice - Zatecka, E; Ded, L; Elzeinova, F; Kubatova, A; Dorosh, A; Margaryan, H; Dostalova, P; Korenkova, V; Hoskova, K; Peknicova, J (Reproductive toxicology (Elmsford, N.Y.), 2014)
We tested the effect of two different concentrations (150μg/l and 0.15μg/l) of mycotoxin zearalenone (ZEA) on the reproductive parameters and expression of testicular genes in male mice. In adult males, no reduction of body or reproductive organ weight was observed, and the seminiferous tubules were morphologically normal with ongoing spermatogenesis. However, we found decreased sperm concentration, increase of morphologically abnormal spermatozoa and increased binding of apoptotic marker annexin V. This study was also focused on the evaluation of gene expression profiles of 28 genes playing important roles during the processes occurring in the testicular tissue. We detected changes in the expression of genes important for proper spermatogenesis. Surprisingly, we observed a stronger effect after exposure to the lower dose of ZEA.
Keywords: exprese genu; Gene Expression; Fertility; Male; Gene expression; Estrogens, Non-Steroidal; spermatogeneze; Reproductive parameters in male mice; Spermatozoa; qPCR; Spermatogenesis; mužské pohlaví; Testis; Animals; nesteroidní estrogeny; Zearalenone; zearalenon; zvířata; testis; spermie; myši; apoptóza; Mice; Apoptosis